Usporedna analiza AAA protokola za rad u bežičnim mrežama : magistarski rad - Stanke, Mladen; Jeren, Branko (Zagreb : M. Stanke ; Fakultet elektrotehnike i računarstva, 2009)
U ovom istraživanju se na praktičnom slučaju istraživala razlika u Diameter i RADIUS protokolu te njihovo ponašanje u stvarnoj situaciji. Testna okolina je realizirana pomoću VitalAAA programa u kojem su podržani RADIUS server i klijent, te Diameter server i klijent. Iz logova se očitavalo vrijeme reakcije u pojedinim mjerenjima. Mjerena su: vremena uspostava spajanja kod RADIUS i Diameter protokola, vrijeme reakcije klijenta na događaj da primarni server nije dostupan, pouzdanost transporta kod Diametera i RADIUS-a, te sposobnost pronalaženja čvora kod Diametera. Rezultati su prikazani tablično, grafički i komentirani.
Ključne riječi:
RADIUS – Remote Authentication Dial-In Services;
Diameter- AAA protokol;
server – odgovoran je za primanje korisničkih zahtjeva, autentifikaciju korisnika i vraćanje svih potrebnih informacija za klijenta da bi omogućio korisniku uslugu;
klijent – odgovoran je za prosljeđivanje korisničkih informacija serveru i mora reagirati na odgovor koji se vratio sa servera;
AAA- Authentication, Authorization and Accounting;
AVP- Attribute Value Pair;
EAP- Extensible Authentication Protocol;
EAP-TLS - EAP-Transport Layer Security;
EAP-TTLS - EAP-Tunneled Transport Layer Security;
VPN- virtual private network;
UDP- User Datagram Protocol;
TCP- Transmission Control Protocol;
TACACS+ - Terminal Access Controller Access-Control System
In this research, the differences between the Diameter and the RADIUS protocols were studied on a practical example, and their behavior was tested in a real life situation. Diameter and the RADIUS test environment was created via the VitalAAA program which supports the RADIUS server and client, and the Diameter server and client. The reaction time for individual measurements was read from the log file. The following measurements were made: connection times for RADIUS and Diameter protocols, client reaction time in case primary server is unavailable, transport reliability for Diameter and RADIUS, and node search capability for Diameter. The results are presented both tabular and graphically and also commented.
Keywords:
RADIUS – Remote Authentication Dial-In Services;
Diameter- AAA protocol;
server - responsible for receiving user connection requests, authenticating the user, and then returning all configuration information necessary for the client to deliver service to the user;
client - responsible for passing user information to servers, and then acting on the response which is returned;
AAA- Authentication, Authorization and Accounting;
AVP- Attribute Value Pair;
EAP- Extensible Authentication Protocol;
EAP-TLS - EAP-Transport Layer Security;
EAP-TTLS - EAP-Tunneled Transport Layer Security;
VPN- virtual private network;
UDP- User Datagram Protocol;
TCP- Transmission Control Protocol;
TACACS+ - Terminal Access Controller Access-Control System
Bibliografija str. 82